Social determinants of health literacy among parents and caregivers in the US-Affiliated Pacific. - Cruz, Rica Dela; Galbreath, Jennifer; Butel, Jean; Yamanaka, Ashley B; Wilkens, Lynne R; Aflague, Tanisha; Coleman, Patricia; Shallcross, Leslie; McFall, Pauline; Novotny, Rachel (Health Promotion International, 2024)
Health literacy is understudied in the US-Affiliated Pacific (USAP), where local populations have historically experienced social marginalization and disproportionate health inequities caused by the social determinants of health (SDOH). This cross-sectional study analyzed several SDOH indicators—acculturation, use of food assistance programs and demographic characteristics (race and ethnicity, household income, primary language spoken at home and educational attainment)—and their relationship to health literacy among 1305 parents/caregivers of young children ages 2–8 years old who participated in the Children's Healthy Living (CHL) program in Alaska, American Samoa, Commonwealth of the Northern Mariana Islands (CNMI), Guam, and Hawai'i. Significantly increased odds of low health literacy were found among parents/caregivers with households where a language other than English was the primary language compared to English-only households (OR = 1.86, 95% CI = 1.22, 2.82), household income of <$35 000 compared to ≥$35 000 (OR = 2.15, 95% CI = 1.13, 4.07), parents/caregivers of Asian children compared to parents/caregivers of White children (OR = 2.68, 95% CI = 1.05, 6.84), parent/caregivers with less than or some high school education compared to high school completion (1st- to 8th-grade OR = 4.46, 95% CI = 2.09, 9.52; 9th- to 11th-grade OR 1.87, 95% CI = 1.06, 3.30) and parent/caregivers with acculturation status defined as marginalized as compared to integrated (OR = 2.31, 95% CI = 1.09, 4.86). This study indicates that some USAP parents/caregivers may lack the capacity to acquire health information, utilize health resources, and navigate health decision making. Future efforts to understand and improve health literacy in the USAP should be population specific, thoroughly assess personal and organizational health literacy, and inventory community health care capacity.